Minization and Maximization of Quasi-Supermodular Functions - Aragonés Salazar, Nelson Omar (2018)
This article presents some properties of the casisupermodular function and demonstrates principles of discarding to solve the problem of minimization and maximization of this type of function defined in the family of subsets of a given finite set (finite boolean lattice); these principles are generalized, in the case of minimization, to a relatively complemented finite lattice. This work extends some results obtained by V.R. Khachaturov and R.V. Khachaturov for the case of supermodular functions.